2020
DOI: 10.3390/toxics8010012
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Inactivated Bifidobacterium Strain in Attenuating Benzo(A)Pyrene Exposure-Induced Damage in Colon Epithelial Cells In Vitro

Abstract: Long-term exposure to benzo(a)pyrene (BaP) poses a serious genotoxic threat to human beings. This in vitro study investigated the potential of inactivated Bifidobacterium animalis subsp. lactis BI-04 in alleviating the damage caused by BaP in colon epithelial cells. A concentration of BaP higher than 50 μM strongly inhibited the growth of colon epithelial cells. The colon epithelial cells were treated with 50 μM BaP in the presence or absence of inactivated strain BI-04 (~5 × 108 CFU/mL). The BaP-induced apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that L. rhamnosus GG and its metabolites can inhibit cytokine-induced apoptosis of human or mouse intestinal epithelial cells by downregulating the p38/MAPK activation and upregulating the PI3K/AKT cascade [ 31 ]. Bifidobacterium animalis subsp lactis BI-04 can delay benzo [a] pyrene (BAP)-induced apoptosis of colon epithelial cells by upregulating the PI3K/AKT signaling pathway and downregulating p53 gene expression [ 32 ]. In this study, H22 hepatoma cells treated with B. coagulans MZY531 showed a concentration-dependent reduction in the expression of p-PI3K, p-AKT and p-mTOR compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that L. rhamnosus GG and its metabolites can inhibit cytokine-induced apoptosis of human or mouse intestinal epithelial cells by downregulating the p38/MAPK activation and upregulating the PI3K/AKT cascade [ 31 ]. Bifidobacterium animalis subsp lactis BI-04 can delay benzo [a] pyrene (BAP)-induced apoptosis of colon epithelial cells by upregulating the PI3K/AKT signaling pathway and downregulating p53 gene expression [ 32 ]. In this study, H22 hepatoma cells treated with B. coagulans MZY531 showed a concentration-dependent reduction in the expression of p-PI3K, p-AKT and p-mTOR compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Inactivated Bifidobacterium detoxified BaP and mitigated the damage it caused to colonic epithelial cells in vitro. [ 15 ] However, BaP adsorption and removal by Lactobacillus in vivo is unclear. Hence, the present study established a model wherein subchronic CICC 23121 infection was induced in mice for 28 d and its efficacy at alleviating oral BaP toxicity was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression level of CYP1A1 was determined by real‐time fluorescence qRT‐PCR using β‐actin as an internal reference gene. [ 15 ] RNA was extracted with a UNIQ‐10‐column TRIzol total RNA extraction kit (Sangon; Beijing, China). The sequences of the upstream and downstream CYP1A1 primers were 5’‐TGCCCTTCATTGGTCACATG‐3’ and 5’‐CACGTCCCCATACTGCTGACT‐3’, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…lactis BI-04 strain can retard Benzo(a)pyrene (BaP)-induced apoptosis of the colonic epithelial cells by up-regulating the PI3K/Akt signaling pathway and down-regulating p53 gene expression. 56 In light of these findings, some researchers have hypothesized that the induction of apoptosis in the SW480 cell line could occur in the presence of heat-killed preparations of Saccharomyces cerevisiae through enhanced expression of BAX, cleaved caspase-3, and cleaved caspase-9 and reduced expression of p -Akt1, Bcl-XL, pro-caspase 3 and 9, which are involved in the Akt/NF-κB signaling pathway. 36 Therefore, by targeting apoptosis and survival-related signaling pathways these probiotics may offer important therapeutic options for cancer management.…”
Section: Probiotics Autophagy and Apoptosismentioning
confidence: 99%